Radiation exposure of personnel and public of radiation control areas of radiation hazardous facilities in the Russian Federation in 2021 - A. N. Barkovsky; R. R. Akhmatdinov; A. M. Biblin; A. G. Sivenkov; A. G. Tsovyanov; V. E. Zhuravleva; S. I. Kuvshinnikov; O. E. Tutelyan (Радиационная гигиена)
The article presents analysis of exposure doses to the population of observation zones and personnel of radiation facilities of the Russian Federation in 2021. For the analysis, we used data received by the Federal Data Bank on Personnel Exposure Doses, which operates as part of the Unified System of Individual Dose Control of the Russian Federation citizens. Data received from 20 359 radiation facilities were used. Among them, there are 19 743 radiation hazardous facilities supervised by Rospotrebnadzor and 616 supervised by the FMBA of Russia. 15 883 (78%) radiation hazardous facilities are medical institutions. In total, in 2021, the Federal Data Bank on Personnel Exposure Doses received the results of measuring the annual individual effective doses of technogenic industrial exposure of 239 743 persons of group A personnel and 22 490 persons of group B personnel. 12 095 people of group A personnel who worked part-time at several radiation facilities were identified The average annual effective dose of technogenic occupational exposure of group A personnel in 2021 was 1.12 mSv, and for group B personnel, whose exposure doses were obtained according to instrumental control data – 0.61 mSv. The maximum values of the average annual effective dose of technogenic occupational exposure for group A personnel in 2021 took place in the Zabaykalsky Krai (2.81 mSv), Perm Krai (2.60 mSv), the Ulyanovsk region (2.03 mSv), the Yamalo-Nenets Autonomous Okrug (1.93 mSv) and the Republic of Buryatia (1.91 mSv). The average individual annual effective dose of technogenic occupational exposure for part-time workers in 2021 was 1.92 mSv/year. It’s in 1.7 times higher compared to personnel A group. In 2021, two cases of exceeding the annual individual dose of 20 mSv and one case of exceeding the annual individual dose of 50 mSv for group A personnel and 12 cases of exceeding the annual individual dose of 5 mSv for group B personnel were identified. The annual individual dose of technogenic occupational exposure of 51.0 mSv (exceeding the dose limit for group A personnel) was registered in the Production association “Sevmash” in the Arkhangelsk region. In 2021, 1.54 million people lived in the radiation control areas of category I of potential hazard radiation facilities. The average annual effective dose of technogenic exposure to this category of the population due to the operation of radiation facilities was 0.018 mSv, which is only 1.8 times higher than the annual effective dose of 0.01 mSv, corresponding to a negligible radiation risk and 55 times less than the average annual dose limit for the population, equal to 1.0 mSv. In general, the radiation situation at the radiation facilities of the Russian Federation is quite stable and complies with safety requirements. Technogenic exposure of the population and personnel due to the normal operation of technogenic sources of ionizing radiation is the least significant radiation factor, both for individual exposure doses and for the collective exposure dose to the population of the Russian Federation. In 2021, only less than 24 thousand persons of group A personnel received annual effective dose of technogenic occupational exposure exceeding 2.0 mSv, which is comparable to the average annual effective dose of natural exposure (3.36 mSv) received by the entire population of Russia. The collective annual effective dose to the population of the Russian Federation due to the operation of radiation facilities in 2021 was less than 0.1% of the dose from all sources.